МЕТОД ПРОЕКТІВ ЯК ЗАСІБ ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ У ПРОЦЕСІ ВИВЧЕННЯ КУРСУ «ІНФОРМАЦІЙНІ СИСТЕМИ ТА МЕРЕЖІ» (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2011)
The article analyzes the essence of project method as the means of learning of students of specialty »Officemanager» in the process of studying the course «Information systems and networks, its maintasks, functions, stages of implementation and conditions of the learning process to ensure quality teachingand learning for teaching the subject.